2013
DOI: 10.3390/educsci3030259
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Educational Benefits from the OpenOrbiter Space Program

Abstract: This paper analyzes the educational impact of the OpenOrbiter Small Spacecraft Development Initiative, a CubeSat development program underway at the University of North Dakota. OpenOrbiter includes traditional STEM activities (e.g., spacecraft engineering, software development); it also incorporates students from non-STEM disciplines not generally involved in aerospace engineering projects such as management, entrepreneurship, education and fine arts. The value of the program to participants is analyzed quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…OpenOrbiter's goals, informed by student participation expectations [28], include [29,30] The CSCI 297 course aims to augment:…”
Section: Student Learningmentioning
confidence: 99%
“…OpenOrbiter's goals, informed by student participation expectations [28], include [29,30] The CSCI 297 course aims to augment:…”
Section: Student Learningmentioning
confidence: 99%
“…Another team from the Jet Propulsion Laboratory has summarized the main working philosophy for CubeSats in Reference [7]. A group of researchers from North Dakota State University have developed the concept of open source satellite [8][9][10][11]. Their goal is to improve the educational output of Nanosatellite hands-on projects by providing reference design models (without getting into the details of technical outcomes or programmatic aspects) and harmonizing hardware, software, testing procedures, and operations.…”
Section: Introductionmentioning
confidence: 99%
“…This list is based on pre-identified project goals and other benefits that students indicated they believed they had received or would like to receive through other surveys [38] The responses of students to this question are summarized in Figures 1-3. Figure 1 presents overall counts of the number of respondents who indicated that they hoped to gain each particular area of benefit.…”
Section: Data Collectedmentioning
confidence: 99%
“…The OpenOrbiter/OPEN spacecraft design is described in [36]. The program [37], which incorporates students from both typical STEM disciplines and others, has demonstrated the efficacy of small spacecraft development for delivering educational benefits to students [38].…”
Section: Openorbiter Programmentioning
confidence: 99%